When no treatment is the best treatment: Active surveillance strategies for low risk prostate cancers. (July 2017) - Stavrinides, V.; Parker, C.C.; Moore, C.M.
Highlights: Active surveillance is a standard approach for managing low grade, organ-confined prostate cancers. Careful selection and close monitoring of eligible patients is necessary. Magnetic resonance imaging is a useful tool for stratifying risk and for monitoring men on active surveillance. Abstract: Although the incidence of prostate cancer is rising due to PSA screening and increased life expectancy, the metastatic potential of low-grade, organ-confined disease remains low. An increasing number of studies suggest that radical treatment in such cases confers little or no survival benefit at a significant cost to morbidity. Active surveillance is a promising management approach of such low-risk cancers: eligible patients are selected based on clinical and pathological findings at diagnosis and are regularly monitored with digital rectal examinations, PSA testing and biopsies. Treatment, however, is deferred until and unless there is evidence of disease progression. This is a key difference from watchful waiting, where treatment is avoided until and unless there are symptoms. The purpose of this work is to review the rationale and evidence behind active surveillance and to offer an overview of current active surveillance strategies and outcomes.